2014
DOI: 10.4097/kjae.2014.67.1.38
|View full text |Cite
|
Sign up to set email alerts
|

The effects on Apgar scores and neonatal outcomes of switching from a combination of phenylephrine and ephedrine to phenylephrine alone as a prophylactic vasopressor during spinal anesthesia for cesarean section

Abstract: BackgroundEphedrine, unlike phenylephrine, has a dose-related propensity to depress fetal pH during spinal anesthesia during cesarean section. A low arterial umbilical cord pH has a strong association with neonatal mortality and morbidity. The purpose of this retrospective study was to investigate influences of vasopressor change on Apgar scores and adverse neonatal outcomes in cesarean section.MethodsIn obstetric anesthesia, we changed the prophylactic vasopressor from a combination of phenylephrine and ephed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…Hypotension that occurred despite phenylephrine infusion was treated with a bolus of 100 µg phenylephrine if the patient's HR was ≥ 60 bpm. In contrast, if the HR was < 60 bpm, then a bolus of 10 mg ephedrine was administered [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…Hypotension that occurred despite phenylephrine infusion was treated with a bolus of 100 µg phenylephrine if the patient's HR was ≥ 60 bpm. In contrast, if the HR was < 60 bpm, then a bolus of 10 mg ephedrine was administered [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, four neonates (2.8%) had Apgar scores of <7 at the first minute, and no neonates had Apgar scores of <7 at the fifth minute. Jeon et al [29], who included more than 3700 patients in their study, showed a significant increase in the incidence of neonates with Apgar scores <7 at the first minute in parturients who received ephedrine plus phenylephrine infusion but not with phenylephrine infusion alone.…”
Section: Discussionmentioning
confidence: 96%
“…Cardiac output studies have shown that SA has a biphasic effect, in which cardiac output initially increases following a reduction in afterload from arterial vasodilatation and subsequently decreases due to a reduced preload [2]. Hypotension affects both the mother and fetus, including maternal nausea, vomiting, dizziness, rare loss of consciousness, cardiac arrest, and death [27]; and fetal symptoms, including low Apgar scores and low umbilical arterial pH (umbilical acidosis), have been shown to be associated with the duration and severity of hypotension [28]. Hypotension may be related to maternal and neonatal morbidity.…”
Section: Introductionmentioning
confidence: 99%